2022
DOI: 10.18332/ejm/145789
|View full text |Cite
|
Sign up to set email alerts
|

The effect of formal fetal movement counting on maternal psychological outcomes: A systematic review and meta-analysis

Abstract: INTRODUCTION Formally counting fetal movements in pregnancy is one of the oldest methods to assess fetal well-being. Although not routinely recommended in contemporary maternity care, due to a lack of evidence of its effectiveness, formal fetal movement counting is still practiced in many birth settings. Requesting women to formally count their fetal movements in a structured, objective way that can potentially improve maternal subjective outcomes such as worry or concern. The aim of this study was to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The movement of the fetus that is felt gives the mother confidence that the fetus exists and is alive, will instinctively stimulate the mother to move, stroke, talk so that the fetus responds with further movements. This maternal-fetal emotional connection has a positive impact on the uteroplacental circulation so that the fetus is maintained healthy (Delaram et al, 2018;AlAmri & Smith, 2022). The results of a study were also reported which stated that counting fetal movements affects the attitudes and actions of mothers who pay more attention to the fetus which has an impact on the development of the fetus to the baby (Yani et al, 2021).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…The movement of the fetus that is felt gives the mother confidence that the fetus exists and is alive, will instinctively stimulate the mother to move, stroke, talk so that the fetus responds with further movements. This maternal-fetal emotional connection has a positive impact on the uteroplacental circulation so that the fetus is maintained healthy (Delaram et al, 2018;AlAmri & Smith, 2022). The results of a study were also reported which stated that counting fetal movements affects the attitudes and actions of mothers who pay more attention to the fetus which has an impact on the development of the fetus to the baby (Yani et al, 2021).…”
Section: Introductionmentioning
confidence: 94%
“…Pregnancy is an important situation in a mother's life that requires physiological and psychological adaptation. Pregnancy adaptation is an important basis for the mother to build a relationship with the fetus during pregnancy (AlAmri & Smith, 2022;Berthelot et al, 2020). Maternal-Fetal Attachment (MFA) is a bond of attachment between mother and baby with love and affection, plays an important role in the health of the mother and fetus and influences the mother's decision to behave healthily during pregnancy, this was revealed in research (Wahyuntari & Puspitasari, 2021;Purwati et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations